FORMATION OF HUMAN CAPITAL IN THE CONTEXT OF DEVELOPMENT OF THE MARKET OF MEDICAL SERVICES IN UZBEKISTAN (Scientific electronic journal "Labor Economics and Human Capital", 2023)
This article is devoted to the formation of human capital in the field of medical services, a synthesis of numerous foreign works on the theory and practice of the formation of human capital and its role in economic development, the medical services market is classified taking into account human capital, and an analysis of the development of the medical services market is carried out.
Keywords: Healthcare, medical services market, human capital, provision of medical services.